Improving social communication skills of children with autism through sibling-mediated playgroup - Reyes, Alyssa Judith S.; Vidal, Lutze-Sol Aplaon; Oael, Irene C.; Olegario, Lizamarie C.; Cauyan, Jaclyn Marie L. (Quezon City College of Education, University of the Philippines Diliman, 2021)
This study examines the impact of Sibling-Mediated Playgroup (SMP) to four sibling pairs of children with autism (CWA) and their typically developing siblings (TDS) in terms of five social communication skills: attention and engagement , sibling initiation, sibling response, and the frequency and duration of communication. Data collection for this study was done in three phases. The Pre-intervention (Pre) phase, the seven-week SMP (intervention), and the Post-intervention (Post). Based on the results of the social communication ratings, the study revealed that after the program, there were improvements in all the five target social skills among the CWA. Similarly, the researcher have observed positive changes in the siblings' relationships such as improved awareness of the TDS on the needs of CWA and the better communication due to the strategies learned in the program. Parents also reported that through the intervention, the sibling pairs were able to connected through their shared experiences. They noted that after the intervention, there were fewer arguments and that the family generally had better family relationships. In addition, the TDS also described their personal experiences and their interaction with CWA during the play sessions. First, they described their experiences with feelings of excitement over shared activities. Second, they gained confidence in leading CWA during the activities. Third, that they liked being an influence to their partner CWA as they learned to interact and play with them. Lastly, the TDS expressed their preference in engaging with cooperative than competitive activities and they felt happy and satisfied working together with their partner CWA.
Thesis
Includes bibliographical references (pages 237-262)
Keywords: Special education -- Parent participation -- Philippines -- Paranaque City; Special education -- Sibling participation -- Philippines -- Paranaque City; Autistic children -- Education (Elementary) -- Philippines -- Paranaque City; Interpersonal communication .; Autistic children -- Family relationships